The Impact of Stress on The Work Performance of COVID-19 Isolation Room Nurses at Hospitals in Timor - Antonius Rino Vanchapo; Anggorowati Anggorowati; Ni Made Merlin (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
The incidence of Corona Virus Disease (COVID-19) in East Nusa Tenggara has increased tremendously since April 2020. This has caused nurses to experience anxiety and stress due to fears of a shortage of special COVID-19 inpatient rooms. This study aimed to analyze the correlation between stress and the work performance of the COVID-19 isolation room nurses in mainland Timor. This cross-sectional study involved 278 nurses who worked in the COVID-19 isolation rooms of three hospitals on Timor Island. The Depression Anxiety Stress Scales (DASS-42) and the Nurse Work Performance Sheet were applied to obtain the data. The results demonstrated that 64 respondents exhibited severe stress which 53 showed poor performance and 11 displayed adequate performance. There was a relationship between work stress and the work performance of the COVID-19 isolation room nurses (p-value = 0.001). This study did not measure other variables that are most likely correlated with work performance, but the result indicates the need for treatments for the nurses who work in such rooms to prevent worse conditions.Abstrak Dampak Stres terhadap Performa Kerja Perawat di Ruang Isolasi COVID-19 di Rumah Sakit di Timor. Kejadian Corona Virus Disease (COVID-19) di Nusa Tenggara Timur telah meningkat pesat sejak April 2020. Hal ini menyebabkan perawat mengalami kecemasan dan stres akibat kekhawatiran akan kekurangan ruang rawat inap khusus COVID-19. Penelitian ini bertujuan untuk menganalisis hubungan antara stres dan performa kerja perawat ruang isolasi COVID-19 di daratan Timor. Penelitian cross-sectional ini melibatkan 278 perawat yang bekerja di ruang isolasi COVID-19 pada tiga rumah sakit yang berada di Pulau Timor. Skala Depression Anxiety Stress Scales (DASS-42) dan Lembar Performa Kerja Perawat digunakan untuk memperoleh data. Hasil penelitian menunjukkan bahwa 64 responden mengalami stres berat. Sebanyak 53 responden menunjukkan performa kerja yang buruk dan 11 responden menunjukkan performa kerja yang memadai. Terdapat hubungan antara stres kerja dengan performa kerja perawat ruang isolasi COVID-19 (p-value = 0.001). Penelitian ini tidak mengukur variabel lain yang kemungkinan besar berkorelasi dengan performa kerja, tetapi hasil penelitian ini mengindikasikan perlunya penanganan bagi perawat yang bekerja di ruang isolasi untuk mencegah kondisi yang lebih buruk terjadi. Kata Kunci: COVID-19, performa kerja, stress